Policing a pandemic: investigating San Antonio's response to COVID-19's new crime of public health violations. (2nd November 2022) - Leal, Wanda E.; Piquero, Alex R.; Piquero, Nicole Leeper
ABSTRACT: After the novel coronavirus began spreading across the U.S., many state and local governments imposed COVID-19 restrictions in an attempt to slow the spread. These COVID-19 mitigation techniques had a large impact on policing, as they created a new crime category for police to enforce, COVID-19 public health violations. The current study aims to address some of the uninvestigated questions about policing a pandemic using a unique dataset that combines three sources of official data from San Antonio, Texas. Specifically, we examine the associations between enforcement of COVID-19 public health violations, police calls for service, and COVID-19 case numbers. We also test for interactions between COVID-19 case numbers and police calls for service with respect to a change in the enforcement of COVID-19 public health violations. Results indicate that both police calls for service and COVID-19 case numbers are significantly associated with enforcement activities for COVID-19 public health violations. Additionally, enforcement is conditioned by the amount and type of police calls for service. Policymakers should consider the work and responsibilities the agencies they expect to enforce these COVID-19 policies already have. Haphazardly assigning an agency, such as the police, this new role without carefully considering whether they can feasibly take on more could lead to less enforcement of the COVID-19 restrictions.